EVIDENCE FOR HIGH IRON REQUIREMENTS OF COLONIAL PHAEOCYSTIS ANTARCTICA AT LOW IRRADIANCE - Sedwick P.N.; Garcia N.S.; Riseman S.F.; Marsay C.M.; Ditullio G.R. (My University, 2007)
We have carried out field and laboratory experiments to examine the iron requirements of colonial Phaeocystis antarctica in the Ross Sea. In December 2003, we performed an iron/light-manipulation bioassay experiment in the Ross Sea polynya, using an algal assemblage dominated by colonial Phaeocystis antarctica, collected from surface waters with an ambient dissolved Fe concentration of ~0.4 nM. Results from this experiment suggest that P. antarctica growth rates were enhanced at high irradiance (~50% of incident surface irradiance) but were unaffected by iron addition, and that elevated irradiance mediated a significant decrease in cellular chlorophyll a content. We also conducted a laboratory iron dose–response bioassay experiment using a unialgal, non-axenic strain of colonial P. antarctica and low-iron (<0.2 nM) filtered seawater, both collected from the Ross Sea polynya in December 2003. By using rigorous trace-metal clean techniques, we performed this dose–response iron-addition experiment at ~0°C without using organic chelating reagents to control dissolved iron levels. At the relatively low irradiance of this experiment (~20 μE m−2 s−1), estimated nitrate-specific growth rate as a function of dissolved iron concentration can be described by a Monod relationship, yielding a half-saturation constant with respect to growth of 0.45 nM dissolved iron. This value is relatively high compared to reported estimates for other Antarctic phytoplankton. Our results suggest that seasonal changes in the availability of both iron and light play critical roles in limiting the growth and biomass of colonial Phaeocystis antarctica in the Ross Sea polynya.
Keywords: IRON; LIGHT; PHAEOCYSTIS ANTARCTICA; ROSS SEA